2004
DOI: 10.1001/archinte.164.17.1866
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hospitalist Attending Physicians on Trainee Satisfaction With Teaching and With Internal Medicine Rotations

Abstract: Trainees reported more effective teaching and more satisfying inpatient rotations when supervised by hospitalists. This analysis suggests that hospitalists may possess or accrue a specific inpatient knowledge base and teaching skill that distinguishes them from nonhospitalists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 25 publications
3
70
0
1
Order By: Relevance
“…This concept of knowledge transmission model of teaching is not always compatible with the dynamic and adaptive concept of learning of the students. Clinical training satisfaction was (58.27%) is in line with other studies [45,46]. Delany and Bragge [44] described a key of recommendations can be used to improve the quality of clinical education introduced to our students, these recommendations firstly seeking harmony between students' and educators' description and understanding of their role in clinical education setting.…”
Section: Discussionsupporting
confidence: 83%
“…This concept of knowledge transmission model of teaching is not always compatible with the dynamic and adaptive concept of learning of the students. Clinical training satisfaction was (58.27%) is in line with other studies [45,46]. Delany and Bragge [44] described a key of recommendations can be used to improve the quality of clinical education introduced to our students, these recommendations firstly seeking harmony between students' and educators' description and understanding of their role in clinical education setting.…”
Section: Discussionsupporting
confidence: 83%
“…To our knowledge, this is the first attempt to confirm or quantify the strength of this correlation. [1][2][3][9][10][11] Role models have an impact on the development of future members of the profession. Role models influence career choice and may facilitate the professional growth of medical trainees, perhaps even more so for women and underrepresented minorities in medicine.…”
Section: Discussionmentioning
confidence: 99%
“…On the monthly evaluations at the University of California, San Francisco (San Francisco, CA), residents' satisfaction with their attendings was significantly higher when the physician was a hospitalist rather than a traditional faculty member. 22 Residents believed hospitalists were more effective teachers, and provided more effective feedback. At Emory University (Atlanta, GA), a methodologically more rigorous study of postrotation assessment of faculty demonstrated that ratings of hospitalists were not different from traditional general internists; both scored higher than subspecialists.…”
Section: Discussionmentioning
confidence: 99%